The nucleotide changes within HBV core promoter/precore during the first 12weeks of nucleos(t)ide treatment might be associated with a better virological response - Yaqin Peng; Yutang Li; Jinlin Hou; Jian Sun; Mingze Su; Li, Yao; Kuanhui Xiang; Ling Yan; Hui Zhuang; Li, Tong (Infect Genet Evol, 2017)
Objectives: We aimed to study the dynamic changes of hepatitis B virus (HBV) core promoter/precore (CP/preC) sequences during antiviral treatment and their associations with virological responses. Materials and methods: The baseline and 12-week CP/preC sequences (nts 1655-2014) were obtained from 52 chronic hepatitis B patients with positive hepatitis B e antigen (HBeAg), who received a 104-week lamivudine and adefovir dipivoxil combination therapy. The mutations within the CP/preC were analyzed against genotype specific reference sequences. The nucleotide change rates in individuals during therapy were analyzed in a pairwise comparison manner. Results: There was no significant difference of the mutation rate at each nucleotide site between baseline and week 12 of treatment (P>0.05). The mutation rates of A1762T/G1764A and G1896A were found to decrease from 46.2% (24/52) at baseline to 36.5% (19/52) at week 12 (P=0.426) and from 28.8% (15/52) to 21.2% (11/52) (P=0.497), respectively. The nucleotide change rates varied from 0.0% - 7.8% in individuals [0.0% in Group 1 (N=26); 0.3% - 7.8% in Group 2 (N=26)] during the first 12-week treatment. HBV DNA levels in Group 2 were significantly lower than those in Group 1 throughout therapy (P<0.01) (e.g., 1.5±1.3log10 IU/ml vs. 2.6±1.0log10 IU/ml at week 104, P=0.001). At week 104 the rates of HBV DNA undetectable and HBeAg loss in Group 2 were significantly higher than those in Group 1 (P<0.05). Along with the increased nucleotide change rates, the rate of HBV DNA undetectable at week 104 tended to increase (odds ratio=0.323, 95% confidence interval=0.138-0.758, P<0.001). Conclusion: Our findings suggested that the nucleotide changes within HBV CP/preC region during the first 12-week treatment might be associated with a better virological response. Keywords: Antiviral response; Core promoter; Hepatitis B virus; Mutation; Nucleotide change; Precore.